PENGGUNAAN METODE PENUGASAN MELALUI PEMBELAJARAN IPS UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Ikrom, Fadhli Dzil (Journal of Professional Elementary Education, 2025)
Researchers used the Classroom Action Research method to make it easier to prepare research according to the title "Use of Assignment Methods through Social Studies learning to Improve Student Learning Outcomes (Classroom Action Research at SDN Panancangan I, Serang City)". Increasing learning outcomes through social studies learning by applying the assignment method, which can be seen in the pre-cycle average score in class 5, namely 26.6 with completeness, namely 0%, while in cycle I it rose to 51.2, the class average with completeness was 28%, namely 8 students completed the evaluation of their learning outcomes and continued in cycle II, namely the increase in learning results to 65.3, the class average with a completion percentage of 78% (22 students). completed and 6 students not yet completed) and in the last cycle there was a significant increase to 78.6 class average, with 100% student completion. Based on the results of pre-cycle, cycle I, cycle II, up to cycle III, it can be concluded that from the application of the Assignment Method through social studies learning to improve student learning outcomes (Classroom Action Research at SDN Panancangan I, Serang City) there is a graphic increase in learning outcomes in each cycle. The statement of the research results can be declared successful or can be said to be significant through the stages of the cycle.